PENGEMBANGAN PERANGKAT PEMBELAJARAN BERORIENTASI KEMAMPUAN BERKOMUNIKASI ILMIAH PADA SISWA SMK FARMASI ISFI BANJARMASIN - Friesta Ade Monita; Muhammad Rezki Rahman; Diah Elmawati; Sunardi Sunardi (Universitas Lambung Mangkurat, 2021)
This study aims to develop learning tools oriented to scientific communication skills for students of SMK Pharmacy ISFI Banjarmasin using a guided discovery learning model on temperature and heat material. This research was carried out in detail; (1) the validity of the learning tools, (2) the practicality of the learning tools in terms of the implementation of the lesson plans, (3) the effectiveness of the learning tools in terms of students' cognitive learning outcomes, and (4) the achievement of students' scientific communication skills. This research is a development model that refers to the Dick and Carey development model, learning tools developed in the form of teaching materials, lesson plans, worksheets, and THB. The results showed; (1) the validity of the learning tools is categorized as valid, (2) the practicality of the learning tools is considered very good. (3) the effectiveness of learning tools is considered effective, and (4) the achievement of scientific communication skills is considered good. This study shows that the learning tools de-veloped are feasible to be used in the learning process.Keywords: learning tools, guided discovery, scientific communication.AbstrakPenelitian ini bertujuan untuk mengembangkan perangkat pembelajaran berorientasi kemampuan berkomunikasi ilmiah pada siswa SMK Farmasi ISFI Banjarmasin menggunakan model pem-belajaran penemuan terbimbing pada materi suhu dan kalor. Penelitian ini dilaksanakan dengan rincian; (1) validitas perangkat pembelajaran, (2) kepraktisan perangkat pembelajaran yang ditinjau dari keterlaksaan RPP, (3) efektifitas perangkat pembelajaran yang ditinjau dari hasil belajar kognitif siswa, dan (4) pencapaian kemampuan berkomunikasi ilmiah siswa. Penelitian ini merupakan model pengembangan yang mengacu pada model pengembangan Dick and Carey, perangkat pembelajaran yang dikembangkan berupa materi ajar, RPP, LKS, dan THB. Hasil penelitian menunjukan; (1) validitas perangkat pembelajaran berkategori valid, (2) kepraktisan perangkat pembelajaran dinilai terlaksana sangat baik, (3) efektifitas perangkat pembelajaran dinilai efektif, dan (4) pencapaian kemampuan berkomunikasi ilmiah dinilai baik. Penelitian ini menunjukkan bahwa perangkat pembelajaran yang dikembangkan layak untuk digunakan dalam proses pembelajaran.Kata kunci: perangkat pembelajaran, penemuan terbimbing, komunikasi ilmiah.